The Relevance of English Grammar Materials Used at Eed Study Program and Three-Dimensional Grammar Framework: A Case of Passive Voice - Wiwinda Hirliana; I Made Sujana; Atri Dewi Aziz (Jurnal Ilmiah Profesi Pendidikan, 2022)
Grammar is an important language aspect in both spoken and written language uses. However, most students at English Education Department Unram found it difficult to learn. It is shown in their TOEFL achievement. The failure may come from various factors, one of which is learning materials. This study is conducted in order to find out whether the course book used by the English Education students using Three-Dimensional Grammar Framework as this framework is created to achieve balance between grammar and communication because the objectives of learning grammar in university level have not been well achieved by the students. This study is qualitative research. The source of the data in this study is the course book used by EED students at University of Mataram entitled English Grammar 2 and focused on the passive voice materials. The data is collected by using documentation. The result of this study is the course book English Grammar 2 has applied the components of Three-Dimensional Grammar Framework such as forms/structures of passive voice have been presented completely as seen from the curriculum, meaning/semantic and use/pragmatic of passive voice have been presented. However, the uses of passive voice such as (1) when the non-agent is more closely related than the agent to the theme of the text, (2) when the non-agent is participant in the immediately preceding sentence, and (3) the speaker is being tactful and evasive are not presented.